Đề xuất một số biện pháp hướng dẫn học sinh tiểu học đọc hiểu văn bản thơ thiếu nhi mang yếu tố truyện - Nguyễn, Đức Khuông (Tạp chí Giáo dục, 2025)
In the 2018 General Education Curriculum of Vietnam, narrative children’s poetry is a genre that combines poetic form with narrative structure, aligning well with the cognitive and psychological characteristics of primary school students. However, the teaching of this genre remains limited due to a lack of effective instructional methods. This article analyzes the linguistic features of narrative children’s poetry and, based on this analysis, proposes several pedagogical strategies to guide primary students in reading and understanding this form of poetry. By examining key genre characteristics - such as simple language, emotionally rich imagery, memorable rhythm, and playful use of language - the article introduces a variety of effective teaching approaches. These include creative storytelling, role-playing, visual illustration, connecting with personal experiences, exploring poetic language, and rewriting poems. These methods contribute to enhancing students’ reading comprehension, aesthetic appreciation, and creative thinking, while also offering practical implications for teaching and further research in Vietnamese language education.